2010
DOI: 10.1016/j.jebo.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Ostracism and the provision of a public good: experimental evidence

Abstract: We analyze the effects of ostracism on cooperation in a linear public good experiment with fixed partner design. Our results show that introducing ostracism increases contribution levels significantly except in first and last periods. Despite reductions in group size due to ostracism, the net effect on earnings is positive. This effect is in contrast to most alternative mechanisms aimed at increasing cooperation rates studied in the literature on public good experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 45 publications
(9 reference statements)
5
37
1
Order By: Relevance
“…The results presented here are in accordance with the outcomes of different behavioural commitment experiments [6,19,28,29]. High levels of cooperation were observed in a PGG experiment where a binding agreement, which was enabled through a prior communication stage among the members of the group, could be arranged before the PGG interaction occurred [6].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results presented here are in accordance with the outcomes of different behavioural commitment experiments [6,19,28,29]. High levels of cooperation were observed in a PGG experiment where a binding agreement, which was enabled through a prior communication stage among the members of the group, could be arranged before the PGG interaction occurred [6].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, PGG experiments where exclusion of disapproved members (for example, through voting) is allowed, exhibit a high level of contribution and commitment [28,29]. But therein exclusion is carried out after the PGG takes place, towards the observed non-contributors, as in the model of Sasaki & Uchida [39], which is different from our model where restriction occurs before the game takes place.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In addition to depending on the number of norm followers in the community, the severity of social sanctioning is also influenced by equity considerations, leading norm followers to act more strongly against individuals extracting well above the accepted norm (and thus receiving much higher pay-offs [35,36]). Experimental research has shown that the degree to which individuals resent free-riders increases with the ensuing income gap [28].…”
Section: A Model Of Norm-driven Cooperation In the Commons (A) Socialmentioning
confidence: 99%
“…Arguably, such partner choice based on past decisions is an important feature of human social interactions (e.g. friendship and alliances) [34][35][36], and might also have been an important driving force for cooperation during human evolutionary history [37]. The question that arises now is this: why would defectors not invest in a profitable reward fund of their own?…”
Section: Introductionmentioning
confidence: 99%